Motives of high school students to participate in sports - Pavel Šmela; Petra Pačesová; Branislav Antala (Karolinum Press, 2020)
The aim of study is to expand the knowledge of motives of Slovak high school students to participate in sports (at school but also in extracurricular activities after school) and identify the differences between boys and girls in adolescent age. The research group consisted of 318 high school students (boys: n = 154, 16.77 ± 1.01 years old and girls: n = 164, 16.54 ± 1.14 years old) from various areas of Slovakia. The questionnaire Exercise Motivations Inventory was used as the research tool. The questionnaire contains 54 items to which the respondent answers on the Likert scale. Kolmogor-Smirnov's test did not confirm the normality of the research group's data. The nonparametric Mann-Whitney U test was used to evaluate the significance of the differences in motives between girls and boys. For effect size was calculated coefficient r. The most important motive to participate in sport for boys is motive to gain strength and endurance and for girls is motive positive health. We can see significant differences in motives to participate in sports between girls and boys, where boys have higher score in motives affiliation (p = 0.001, r = 0.18), appearance (p = 0.012, r = 0.14), social pressure (p = 0.006, r = 0.15), social recognition (0.001, r = 0.29) and strength and endurance (p = 0.001, r = 0.23). Significantly higher score girls have in motive weight management (p = 0,009, r = 0.15). Our results can help teachers of physical education, trainers, sport educators and parents to plan thematic units, sport activities, which are of interest and attractive in age of adolescence.